ANALYSIS OF EXTRINSIC MOTIVATION IN HONORARIUM TEACHERS (Study on Honor Teachers at SMKN 01 Bengkayang) - Eligia Monixa Salfarini; Blasius Manggu; Jones Parlindungan Nadapdap; Bella Ghia Dimmera (SEAN Institute, 2023)
This study aims to analyze extrinsic motivation among honorarium teachers at SMKN 01 Bengkayang. Based on school data, around 32.5% of teachers are honorarium teachers at SMKN 01 Bengkayang. The involvement of honorarium teachers in fulfilling the availability of teachers in schools is still very much needed, especially in border areas; therefore, it is necessary to analyze extrinsic motivation factors for honorarium teachers. The research method used is the descriptive-qualitative method. The data in this study are primary and secondary. Primary data is data obtained directly from participants through in-depth interviews; this method is used so that the data collected is deeper and more accurate because it comes from direct participants. Secondary data is data that comes from school documents, electronic sources such as dapodik data, and relevant literature that can support this research. The number of participants was six, who had a career as teachers and worked at SMKN 01 Bengkayang for more than 2 years. The results of the analysis show that leaders, the work environment, life needs, and future careers encourage honorarium teachers to remain enthusiastic at work. From the analysis of interviews with honorarium teachers, future careers to become PPPK employees are their main driving force at work, followed by the work environment, and based on the codification analysis of external factors, leadership, and physiology are in the least favorable position as drivers of work motivation for honorarium teachers. The hope of getting the opportunity to become a government contract employee is the main reason for these honorarium teachers to choose to become honorarium teachers and work optimally because their position as honorarium teachers allows them to be accepted as government contract employees with jobs that match their abilities and better compensation.